Integrated Analysis of microRNA-mRNA Expression in Mouse Lungs Infected With H7N9 Influenza Virus: A Direct Comparison of Host-Adapting PB2 Mutants - Guo, Yanna; Huang, Nan; Tian, Miao; Fan, Menglu; Liu, Qingzheng; Liu, Zhiyuan; Sun, Tongtong; Huang, Jingjin; Xia, Huizhi; Zhao, Yongzhen; Ping, Jihui (Frontiers in Microbiology, 2020)
MicroRNAs（miRNAs）are important regulators involved in the antiviral response to influenza virus infection; however, an analytical comparison of miRNA and mRNA expression changes induced by several H7N9 host-adapting PB2 mutants remains undone. Here, miRNA microarray and transcriptome sequencing of BALB/c mouse lungs infected with A/Anhui/1/2013 (H7N9) (hereafter referred to as H7N9/AH1-PB2-627K(WT)) and mutant variants with PB2 amino acid substitutions (avian-like H7N9/AH1-PB2-627E and mammalian-adapted H7N9/AH1-PB2-627E/701N) were directly compared. The results showed that influenza virus infection induced dysregulation of numerous host cell processes. In a miRNA-mRNA network associated with immunity, changes in the expression of 38 miRNAs and 58 mRNAs were detected following influenza virus infection. Notably, the miRNAs mmu-miR-188-5p, mmu-miR-511-5p, mmu-miR-483-5p, and mmu-miR-690 were specifically associated with the replication of the avian-like virus H7N9/AH1-PB2-627E. Likewise, the miRNAs mmu-miR-691, mmu-miR-329-3p, and mmu-miR-144-3p were specifically associated with the mammalian-adapted virus H7N9/AH1-PB2-627E/701N. Finally, the miRNAs mmu-miR-98-5p, mmu-miR-103-3p, mmu-miR-199a-5p, and mmu-miR-378a-3p were specifically associated with H7N9/AH1-PB2-627K(WT) virus replication. This is the first report of comparative integration analysis of miRNA-mRNA expression of these three H7N9 influenza viruses with different host-adapting PB2 mutations. Our results highlight potential miRNAs of importance in influenza virus pathogenesis.